Phantom hand and wrist movements in upper limb amputees are slow but naturally controlled movements. (15th January 2016) - De Graaf, J.B.; Jarrassé, N.; Nicol, C.; Touillet, A.; Coyle, T.; Maynard, L.; Martinet, N.; Paysant, J.
Graphical abstract: Highlights: Phantom limbs can often be moved by will. Phantom finger and global hand movements are frequent. Phantom movements evoke fatigue. Their kinematics can be explored by imitation with the intact limb. Phantom movements are slow but naturally controlled. Abstract: After limb amputation, patients often wake up with a vivid perception of the presence of the missing limb, called "phantom limb". Phantom limbs have mostly been studied with respect to pain sensation. But patients can experience many other phantom sensations, including voluntary movements. The goal of the present study was to quantify phantom movement kinematics and relate these to intact limb kinematics and to the time elapsed since amputation. Six upper arm and two forearm amputees with various delays since amputation (6 months to 32 years) performed phantom finger, hand and wrist movements at self-chosen comfortable velocities. The kinematics of the phantom movements was indirectly obtained via the intact limb that synchronously mimicked the phantom limb movements, using a Cyberglove® for measuring finger movements and an inertial measurement unit for wrist movements. Results show that the execution of phantom movements is perceived as "natural" but effortful. The types of phantom movements that can be performed are variable between the patients but they could all perform thumb flexion/extension and global hand opening/closure. Finger extension movements appeared to be 24% faster than finger flexion movements. Neither the number of types of phantom movements that can be executed nor the kinematic characteristics were related to the elapsed time since amputation, highlighting the persistence of post-amputation neural adaptation. We hypothesize that the perceived slowness of phantom movements is related to altered proprioceptive feedback that cannot be recalibrated by lack of visual feedback during phantom movement execution.